Komunikasi Lingkungan Berbasis Kearifan Lokal dalam Pelestarian Hutan Adat Marena di Kabupaten Enrekang-Indonesia - Harjono, Harya Ningsi; Mustafa, Mustari (Danudirja Setyabudi Nusantara, 2025)
This study analyses the role of local wisdom-based environmental communication in the preservation of the Marena Customary Forest in Enrekang Regency, South Sulawesi, Indonesia. Using a qualitative case study approach, data were collected from non-participant observation, in-depth interviews with 10 traditional leaders (Batu Ariri), community leaders, and conservationists, as well as analysis of traditional documents (Eda wa'ding). The results reveal three key communication patterns: (1) Ritual (offering manuk-lappa lappa to ask for ancestral permission before agricultural activities); (2) Normative (customary prohibitions such as logging/forest burning); and (3) Layered sanctions (gerek tedong pujak—slaughtering a black buffalo for serious violations). Participatory mechanisms such as Si Ottoman Upa (egalitarian decision-making with knees touching) and traditional